Learning as a communal process and as a byproduct of social activism - Matusov, Eugene; St. Julien, John; Lacasa, Pilar; Candela, Maria Alburquerque (Outlines. Critical Practice Studies, 2007)
The purpose of this paper is to draw out the consequences of the communal character of learning approach promoted by a sociocultural framework. This approach has both descriptive-analytical and prescriptive-guiding power: it helps to analyze existing practices be they traditional, exclusive, or innovative but, what is, probably, even more important, it also helps to guide practitioners in the design of more inclusive educational practices. In the first part of the paper, we will provide a framework for analyzing the case of a shift from a traditional institutionalized perspective that understands learning as an individual process located in the head of the learner to the institutionalization of learning as a communal process — a regime which helps avoid constructing children in terms of a deficit model, disability, and academic failure. In the second part of the paper, we will discuss how treating learning as a communal process can guide an educational practitioner to develop a new pedagogical regime of a learning community of social activists that leads to inclusive pedagogy and eliminate “zones of teacher-student disability.